REALISASI BUDAYA POSITIF DAN RELEVANSINYA DENGAN PROFIL PELAJAR PANCASILA DI SEKOLAH DASAR - Suhainah; Sri Erdawati (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2026)
Negative culture is still widely practiced by elementary school students, there are still students who roam outside the classroom during class hours, do not obey school rules, behave impolitely, are irresponsible in doing assignments, litter, speak dishonestly in socializing with fellow students, are reluctant to help friends who have difficulty learning, violate discipline at school. The purpose of this study is to realize a positive culture in realizing the profile of Pancasila students at State Elementary School 023 Tembilahan. The type of research used is qualitative research, with informants of grade IV teachers and grade IV students at State Elementary School 023 Tembilahan. The data in this study came from interviews and documentation, then analyzed using data triangulation. The results, the realization of a positive culture in realizing the profile of Pancasila students through 9 aspects, the realization of an honest attitude in socializing at school, the realization of a culture of mutual trust, the realization of a culture of cooperation, the realization of a culture of reading, the realization of a culture of discipline and efficiency, the realization of a culture of achievement, the realization of a culture of giving awards and reprimands, and the realization of a culture of mutual cooperation. The conclusion of this study is that a positive culture that has been implemented well can realize the profile of Pancasila students at State Elementary School 023 Tembilahan.